Prejudice Reflected in Stephen King's Elevation (2018) : A Sociological Approach - Wisnu Wirawan (Institut Agama Islam Negeri Palopo, 2021)
This study aims to 1) identify indicators of prejudice in the novel. 2) analyze the form of the depiction of prejudice in the novel. And lastly, 3) analyzing the reasons why the author Stephen King included elements of prejudice in the novel Elevation (2018). This study uses a sociological approach. This research is included in qualitative research that focuses on the elements of prejudice in the novel by using descriptive analysis techniques to analyze the data. The researcher found three findings based on the problem statement. First, indicators of prejudice in the novel. Researchers found two indicators of prejudice, namely sexual prejudice and political prejudice. Second, the form of the depiction of prejudice in the novel. There are three instruments used by the author to describe prejudice, namely characters, settings, and events. Third, the reason why the author includes an element of prejudice in the novel is the author's concern about the social situation in the United States at the time the novel was written.